Correlation of Imaging Findings with Molecular Subtypes of Breast Cancer - Panta, Om Biju; Dhakal, Vivek; Gurung, Bibek; Ghimire, Ram Kumar (Journal of Nepal Health Research Council, 2023)
Background: Ultrasound and Mammography are first-line imaging in breast cancer. The management of malignant breast lesions depends on molecular biomarkers in the tumor cells. This study aims to correlate different imaging findings in breast carcinoma with immune-histology subtypes. Methods: The study was a retrospective study conducted between 2018 January to 2021 December. Patients with malignant breast lesions who underwent USG-guided biopsy of breast lesions were included in the study. Ultrasound and mammographic findings of these patients were retrieved in PACS and analyzed. Malignant breast lesions were classified according to molecular markers into Luminal A, Luminal B, Her- 2 enriched, and triple-negative breast cancers. The correlation between imaging findings and molecular subtypes of breast cancer was analyzed. Results: A total of 42 patients were included in the study. The mean age of the patients in our study was 52.24+/-13.54 years with median of 51 years (IQ range-19.5 years). The most common IHC subtype was Luminal type B (22, 52.4%), followed by triple negative (15, 35.7%), luminal type A (4, 9.5%) and least common was Her-2 enriched (1, 2.4%). Mammogram was non-diagnostic in 9.5% of case. Oval shape and well marginated margin in ultrasound were more frequently associated with triple negative breast cancer than other subtypes (P<0.05). Rest of the characteristics of triple negative and other malignancies were not significantly difference in our study. No significant difference is noted between mammographic findings between various subtypes. Conclusions: Triple negative breast cancer was more common in our population than in the west. Triple-negative breast cancers are more frequently well-defined and oval in shape mimicking benign lesions. Keywords: Breast cancer; mammography; molecular subtypes; ultrasound